Beneficial effects of dihydrocapsaicin on paraquat-induced acute kidney injury: role of Sox9/Sesn2 axis-mediated autophagy - Siqi Yu; Fudong Wang; Yuan Zhang; Xiaofeng Wang; Hongyu Zhao; Qiang Zheng (Ecotoxicology and Environmental Safety)
Autophagy inhibition induced by paraquat (PQ) poisoning is an important factor causing multi-organ damage, including renal tissue. Dihydrocapsaicin (DHC), the main active ingredient in chili peppers, was reported to induce autophagy, but its effect on PQ-induced AKI remains unclear. Rats were intraperitoneally injected with 25 mg/kg PQ to establish AKI rat model followed immediately by DHC administration (2.5, 5, or 10 mg/kg, i.p.). Rat renal tubular epithelial cells were exposed to PQ (300 μM) in combination with DHC (25, 50, or 100 μM) for 24 h. The results showed that DHC treatment attenuated PQ-induced renal injury and dysfunction while suppressing apoptosis and oxidative stress in vivo and in vitro. Furthermore, DHC administration induced autophagy—a protective mechanism against oxidative stress and apoptosis—as demonstrated by: 1) increased autophagosome/autophagolysosome formation, 2) upregulated LC3-II and autophagy-related gene 7 expressions and reduced p62 protein level. Blocking of autophagy by 3-methyladenine (3-MA) reversed the effects of DHC. Interestingly, transcription factor sex determining region Y-box 9 (Sox9) and autophagy inducer Sestrin2 RNA levels were increased by DHC treatment. Sox9 activated Sestrin2 transcription through direct binding to its promoter region. Sox9 or Sestrin2 silencing reversed the effects of DHC. Collectively, our findings demonstrate that DHC attenuates PQ-induced AKI via Sox9/Sestrin2 axis-mediated autophagy, indicating therapeutic utility of DHC against AKI.